Results of 15 years of extended follow-up of the German porcelain workers cohort study: lung cancer and silicosis - Birk, Thomas; Mundt, Kenneth A.; Crawford, Lori; Driesel, Patrizia (Frontiers in Public Health, 2025)
ObjectivesTo quantify, after extending follow-up 15 years, the relationship between occupational respirable crystalline silica (RCS) exposure and risk of silicosis diagnosis and lung cancer mortality in the German Porcelain Workers Cohort Study, and to estimate possible exposure thresholds for these.MethodsPorcelain workers enrolled between January 1, 1985, and December 31, 1987, in a mandatory medical surveillance program including triennial chest x-rays and alive at the end of the previous study follow-up (2005) were followed through December 2020, for lung cancer mortality and silicosis incidence. Cause of death was determined from death certificates. Silicosis cases were identified by re-reading x-rays of individuals remaining in the medical surveillance program or filing insurance claims for silicosis. RCS exposure was estimated for each cohort member using a job exposure matrix (JEM) based on about 8,000 historical industrial hygiene RCS measurements. Cause-specific standardized mortality ratios (SMRs) and Cox proportional hazards ratios (HRs) and their 95% confidence intervals (95% CIs) were estimated by cumulative and average exposure groups, controlling for age, sex, smoking status and employment duration. Exposure-response analyses were performed to identify possible exposure thresholds for lung cancer and silicosis risk.ResultsTotal deaths increased from 1,610 (9.1%) to 4,586 (26%) over 537,129 total person-years at risk. All-cause mortality was elevated among men (SMR = 1.10, 95% CI 1.06–1.14); however, a deficit was seen among women (SMR = 0.93, 95% CI 0.89–0.98). No statistically significantly increased mortality was seen due to lung cancer, renal cancer, or non-malignant renal disease – conditions reportedly associated with RCS exposure. Lung cancer mortality was unrelated to RCS exposure level. However, for silicosis cases classified using International Labor Organization (ILO) categories ≥1/1 or 1/0, risk was strongly associated with estimated average exposure >0.10 mg/m3 and 0.15 mg/m3, and cumulative exposure >3.0 mg/m3-years and > 1.0 mg/m3-years, respectively.ConclusionDespite the large number (n = 284) of lung cancer deaths and high historical RCS exposures, no excess risk and no relationship with exposure level were seen. However, RCS exposure was strongly associated with silicosis risk, with clear exposure thresholds. This study further confirms the lack of increased lung cancer risk at RCS levels historically prevalent in the German porcelain industry and that exposures exceeding estimated thresholds clearly increased silicosis risk. Occupational exposure levels in the German porcelain industry in recent decades have remained well below these thresholds; therefore, few additional silicosis cases are expected.